Cloning, expression, and characterisation of a Plasmodium vivax MSP7 family merozoite surface protein (2006)
Plasmodium vivax remains the most widespread Plasmodium parasite specie around the world, producing about 75 million malaria cases, mainly in South America and Asia. A vaccine against this disease is of urgent need, making the identification of new antigens involved in target cell invasion, and thus potential vaccine candidates, a priority. A protein belonging to the P. vivax merozoite surface protein 7 (PvMSP7) family was identified in this study. This protein (named PvMSP71) has 311 amino acids displaying an N-terminal region sharing high identity with P. falciparum MSP7, as well as a similar proteolytical cleavage pattern. This protein’s expression in P. vivax asexual blood stages was revealed by immuno-histochemical and molecular techniques.